Five Years After Child Sexual Abuse - Swanston, Heather Yvette (2000)
Introduction Child sexual abuse is a common problem. Psychological and behavioural problems in children and adults who have experienced child sexual abuse have been associated with the abuse. Little research has been conducted which has been long-term, prospective, involved substantiated sexual abuse, included a control group, took into account mediating factors, utilised multiple data sources, relied on standardised measures and had a high follow-up rate. Aim The aims of this study were to compare a cohort of sexually abused young people with a group of nonabused peers and to establish predictors of psychological and behavioural outcome. Method This study was a follow-up which was long-term, prospective, involved a sample of children with substantiated sexual abuse, included a control group, took into account mediating factors, utilised multiple data sources, relied on standardised measures and had a high follow-up rate. Eighty-four sexually abused young people were followed up five years after presenting to Childrens Hospitals Child Protection Units for sexual abuse and were compared to a group of 84 nonabused young people of similar age and sex. The two groups were compared on the basis of demographic variables, family functioning, mothers mental health and life events; the outcome measures of depression, self-esteem, anxiety, behaviour, criminal activity, alcohol and other drug use, eating problems, running away, suicide attempts, self-injury, hopefulness, despair and attributional style; and potential mediating factors such as further notifications to the Department of Community Services, receipt of psychological treatment, legal action against offenders and victims compensation. Potential predictors of outcome were (1) demographic variables, (2) sexual abuse characteristcs, (3) intake data and (4) five year follow-up variables. Main findings Follow-up rates were 81percent (n equals 68) for cases and 89percent (n equals 75) for controls. Five years after presenting for the sexual abuse, the sexually abused young people were performing more poorly than their nonabused peers on various measures of psychological state and behaviour. Although the abused children had experienced more negative life events (p<.001), were from lower socio-economic groups (p<.0001), had more changes in parent figures (p<.001) and had mothers who were more psychologically distressed (p equals .03), multiple regression analysis showed that after allowing for these and other demographic and family factors, there were still significant differences between the groups after the 5 years. The abused children displayed more disturbed behavior (p equals .002), had lower self-esteem (p<.001), were more depressed or unhappy (p<.001) and were more anxious (p equals .03) than controls. Sexually abused children had significantly higher levels of bingeing (p equals .02), self-injury (p equals.009) and suicide attempts (p equals .03). Significant predictors of psychological and behavioural outcome were significantly related to family and parent functioning variables. Abuse status was not a significant predictor when offered to each of the predictive models. Significant predictors of outcome included the following intake variables: family functioning, mothers mental health, whether parents were employed or not, behaviour scores, prior notifications for neglect, history of parental discord and whether there were caregiver changes or not prior to intake. The classification of the index sexual abuse event as indecent assault and whether there were notifications for sexual abuse prior to the index event also significantly predicted outcome. Five year follow-up variables which were significant predictors of outcome were the young persons age, number of negative life events, attributional style, self-esteem, depression, number of parent changes, anxiety, despair, whether there were notifications for abuse/neglect after intake and having a parent with a history of drug/alcohol problems. Conclusions Difficulties associated with child sexual abuse continue for some years after the abuse event. Child sexual abuse needs to be considered as a possible antecedent of behaviour and psychological difficulties in young people. Treatment and monitoring should continue for some years after the abuse. Treatment may need to be directed more towards young peoples psychological states rather than focusing specifically on the sexual abuse. Family and parent functioning may need to be addressed early in order to prevent some of the behavioural and psychological difficulties associated with the long-term outcome of child sexual abuse